São Miguel dos Campos: a cultural rescue on the timeline / São Miguel dos Campos: um resgate cultural na linha do tempo - Erica Matias dos Santos; Luciano Mendes Duarte Junior; Jhonny Kevin dos Santos Silva; Mirelly de Melo Santos (Universidade Estadual de Alagoas, 2016)
São Miguel dos Campos, a city located in a region called Zona da Mata in Alagoas, has forgotten its cultural identity over the years. A dance called taieira, local legends, and the Bridge Fair are just some of the historical aspects of people from São Miguel do Campos which are put behind and/or moved away from their original features. The present article aims to bring out this overlooked culture and stimulate its appreciation, highlighting some reasons that causes its devaluation. For this, data collection was conducted through oral interviews and literature review. From the data resulting from the analysis it was noticed that people from São Miguel dos Campos has no full knowledge about cultural events that happens in their own city, as well as of the artists born in the city. It happens because, despite the city has a great artistic potential and talented artists, the cultural prospect of São Miguel dos Campos is stagnant and its artists demotivated by lack of incentives and public policies. This problem could be partly solved with investments in cultural attractions cultural attractions that arouse artistic talents of the region and, of course, to bring to public knowledge the existing artists. We share the opinion that people who do not know their culture also does not know their identity. So we hope that this work can contribute positively to instigate new discussion on this issue.